The quality of risk reports: Integrating requirement levels of standard setters into text analysis - Nils Helms; Reinhold Hölscher; Matthias Nelde; Jochen Schneider (Journal of Corporate Accounting & Finance, 2021)
The intention of this paper is to shed light on the analysis of financial disclosure through the integration of requirement levels. This in return will lead to the development of a general applicable evaluation methodology based on Bloom's taxonomy system. Therefore, it will be possible to explicitly consider the relevance of the given information. To underline the appropriateness of our method, we combine the requirement levels with a qualitative content analysis. Based on the German accounting standard DRS 20, we clarify the respective application of the requirement levels in the context of the qualitative content analysis. Hence, we will discuss the limitations of our developed approach. In addition, we analyze further areas of application in the context of qualitative analysis of financial disclosure. All things considered, it is evident that our chosen approach, through the integration of a taxonomy system, contributes to the validity of established text analyzing methods.
Keywords: 650; DRS~20; qualitative content analysis; requirement level; risk report; text analysis